Mechanism of Radix Rhei Et Rhizome Intervention in Cerebral Infarction: A Research Based on Chemoinformatics and Systematic Pharmacology. (7th September 2021) - Xiang, Wang; Long, Zhiyong; Zeng, Jinsong; Zhu, Xiaofei; Yuan, Mengxia; Wu, Jiamin; Wu, Yonghe; Liu, Liang
Abstract : Objective . To explore the therapeutic targets, network modules, and coexpressed genes of Radix Rhei Et Rhizome intervention in cerebral infarction (CI), and to predict significant biological processes and pathways through network pharmacology. To explore the differential proteins of Radix Rhei Et Rhizome intervention in CI, conduct bioinformatics verification, and initially explain the possible therapeutic mechanism of Radix Rhei Et Rhizome intervention in CI through proteomics. Methods . The TCM database was used to predict the potential compounds of Radix Rhei Et Rhizome, and the PharmMapper was used to predict its potential targets. GeneCards and OMIM were used to search for CI-related genes. Cytoscape was used to construct a protein-protein interaction (PPI) network and to screen out core genes and detection network modules. Then, DAVID and Metascape were used for enrichment analysis. After that, in-depth analysis of the proteomics data was carried out to further explore the mechanism of Radix Rhei Et Rhizome intervention in CI. Results . (1) A total of 14 Radix Rhei Et Rhizome potential components and 425 potential targets were obtained. The core components include sennoside A, palmidin A, emodin, toralactone, and so on. The potential targets were combined with 297 CI genes to construct a PPI network. The targets shared by Radix Rhei Et Rhizome and CI include ALB, AKT1, MMP9, IGF1, CASP3, etc. The biological processes that Radix Rhei Et Rhizome may treat CI include platelet degranulation, cell migration, fibrinolysis, platelet activation, hypoxia, angiogenesis, endothelial cell apoptosis, coagulation, and neuronal apoptosis. The signaling pathways include Ras, PI3K-Akt, TNF, FoxO, HIF-1, and Rap1 signaling pathways. (2) Proteomics shows that the top 20 proteins in the differential protein PPI network were Syp, Syn1, Mbp, Gap43, Aif1, Camk2a, Syt1, Calm1, Calb1, Nsf, Nefl, Hspa5, Nefh, Ncam1, Dcx, Unc13a, Mapk1, Syt2, Dnm1, and Cltc. Differential protein enrichment results show that these proteins may be related to synaptic vesicle cycle, vesicle-mediated transport in synapse, presynaptic endocytosis, synaptic vesicle endocytosis, axon guidance, calcium signaling pathway, and so on. Conclusion . This study combined network pharmacology and proteomics to explore the main material basis of Radix Rhei Et Rhizome for the treatment of CI such as sennoside A, palmidin A, emodin, and toralactone. The mechanism may be related to the regulation of biological processes (such as synaptic vesicle cycle, vesicle-mediated transport in synapse, presynaptic endocytosis, and synaptic vesicle endocytosis) and signaling pathways (such as Ras, PI3K-Akt, TNF, FoxO, HIF-1, Rap1, and axon guidance).